LITHOSTRATIGRAPHY AND PLANKTONIC FORAMINIFERAL BIOSTRATIGRAPHY OF THE APTIAN-ALBIAN "SCISTI A FUCOIDI" IN THE PIOBBICO CORE, MARCHE, ITALY: BACKGROUND FOR CYCLOSTRATIGRAPHY (Rivista italiana di Paleontologia e Stratigrafia, 1989)
The Aptian-Albian Scisti a Fucoidi Formation, cropping out widely in the Umbrian-Marchean Basin (Italy), consists of a varicolored pelagic sequence of thinly interbedded red and green marlstones and calcareous marlstones, dark gray to black Corg-rich calcareous shales, and light green-gray marly limestones andlimestones. The variable colored lithotypes appear to be rhythmically deposited. In order to investigate in detail such rhythmicity and the mechanism leading to the accumulation of Corg-rich sediments, a core, the Piobbico core, was speciﬁcally cut through the Scisti a Fucoidi.